Completing a molecular timetree of Afrotheria - Craig, Jack M.; Fisher, Whitney L.; Thomas, Allan S.; Hedges, S. Blair; Kumar, Sudhir (Frontiers in Bioinformatics, 2025)
Afrotheria, the superorder that includes aardvarks, elephants, elephant shrews, hyraxes, manatees, and tenrecs, is home to some of the most charismatic and well-studied animals on Earth. Here, we assemble a nearly taxonomically complete molecular timetree of Afrotheria using an integrative approach that combines a literature search for published timetrees, de novo dating of untimed molecular phylogenies, and inference of timetrees from new alignments. The resulting timetree sheds light on the impact of the Cretaceous-Paleogene (K-Pg) role ∼66 million years ago in the diversification of Afrotherian orders. The earliest divergence in the timetree of Afrotherian mammals predates the K-Pg event by 12 million years, followed by five interordinal divergences that occurred gradually over a 16-million-year period encompassing the K-Pg event.